Determinants of Sustainable Profitability in Indonesian Regional Development Banks During COVID-19 - Devy Mawarnie Puspitasari; Sotarduga Napitupulu (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2026)
Regional Development Banks (BPDs) in Indonesia face the dual responsibility of maintaining profitability while supporting regional economic development, a challenge that intensified during the COVID-19 pandemic. This study aims to examine the financial and governance determinants of sustainable profitability among Indonesian BPDs during the crisis period. Using panel data from 27 BPDs over 2019–2021, this study applies the Fixed Effects Model (FEM) to analyze the effects of capital adequacy ratio (CAR), non-performing loans (NPL), operational efficiency (BOPO), good corporate governance (GCG), and institutional share ownership (ISO) on return on assets (ROA). The results show that CAR has a positive and significant effect on ROA (b = 0.0823; p = 0.001), while NPL (b = -0.2156; p = 0.003) and BOPO (b = -0.0612; p = 0.003) have negative and significant effects. GCG (b = 0.0456; p = 0.019) and ISO (b = 0.0289; p = 0.035) also positively affect ROA. The model explains 72.34% of profitability variation. These findings imply that capital strength, credit risk control, operational efficiency, governance quality, and institutional oversight are essential for sustaining BPD profitability during systemic crises.